STUDI IDENTIFIKASI KESESUAIAN PENGELOLAAN DANA BPJS KESEHATAN DENGAN PRINSIP SYARIAH - Rosmiati Rosmiati; Hasan Aedy; Ambo Wonua Nusantara (Universitas Halu Oleo, 2018)
This study aims to determine the level of suitability of BPJS Health fund management with sharia principles. The design of the study is qualitative descriptive. Data collection is done using interview guide lists. In this study, the informants were 1 person BPJS Health leader, 3 staff employees, 2 directors, and 4 Kendari Health BPJS insurance participants. This study uses descriptive analysis. The results showed that the management of health BPJS insurance funds was known to contain elements of usury. It is said to contain elements of usury because every month the contribution funds that enter the BPJS account are of course certainly getting ziyadah or additional funds as conventional banks in general. The premium system run by BPJS contains things that contain elements of gharar seen from unclear agreements used between participants and the BPJS, containing elements of uncertainty (gambling / maysir) in premium payments and the amount obtained and there are elements of injustice to participants who die the world whose premiums are said to be non-refundable (forfeited), as well as the separation between the poor, middle and upper classes in the facility